Comparison of the impacts of elevated CO₂ soil gas concentrations on selected European terrestrial environments - West, J.M.; Jones, D.G.; Annunziatellis, A.; Barlow, T.S.; Beaubien, S.E.; Bond, A.; Breward, N.; Coombs, P.; de Angelis, D.; Gardner, A.; Gemeni, V.; Graziani, S.; et al. (Elsevier, 2015)
Selected European studies have illustrated the impacts of elevated CO₂ concentrations in shallow soils on pasture. For the first time, general unified conclusions can be made, providing CO₂ thresholds where effects on plants and soil microbiology are observed and making recommendations on how this information can be used when planning projects for CO₂ storage. The sites include those where CO₂ is being naturally released to the atmosphere from deep geological formations; and a non-adapted site, with no previous history of CO₂ seepage, where CO₂ has been injected into the unsaturated soil horizon. Whilst soil gas concentrations will be influenced by flux rates and other factors, the results suggest that a concentration of between 10% and 15% CO₂ soil gas at 20 cm depth, which is within the root zone, is an important threshold level for observing changes in plant coverage. Site-specific plant ‘indicators’ are also observed for CO₂ concentrations at ≥35%. Microbiological changes are seen where CO₂ soil gas concentrations are between 15% and 40%. As part of site characterisation, an evaluation of the risks of leakage and their potential environmental impacts should be undertaken.